Securitizing immigration the politics of risk in the EU - Munster, Rens van 1977- (Palgrave Macmillan, 2009)
"Securitizing Immigration deals with the growing concern for immigration as a matter of security at the EU level. It combines an analysis of the way bureaucratic and political processes have interacted in the integration process with an analysis of how these practices are located in a context shaped by the preoccupation with risk"--Provided by publisher
Includes bibliographical references and index
Machine generated contents note: Introduction * Immigration and the Emergence of a European Threat Environment * The Maastricht Treaty: The Formalization of the Immigration/Security Nexus * Amsterdam and Beyond: Immigration and the Establishment of an AFSJ * Freedom, Mobility and Abjection: The Management of Immigration Risk in the AFSJ * Unmaking Security, Remaking Belonging * Conclusion: The EU as an Area of Security, Security and-- Security Introduction * Immigration and the Emergence of a European Threat Environment * The Maastricht Treaty: The Formalization of the Immigration/Security Nexus * Amsterdam and Beyond: Immigration and the Establishment of an AFSJ * Freedom, Mobility and Abjection: The Management of Immigration Risk in the AFSJ * Unmaking Security, Remaking Belonging * Conclusion: The EU as an Area of Security, Security and-- Security
Keywords: Europäische Union; National security / European Union countries; Risk management / European Union countries; Migration; Politik; National security -- European Union countries; Risk management -- European Union countries; Mitgliedsstaaten; Einwanderungspolitik; Innere Sicherheit; European Union countries / Emigration and immigration; European Union countries / Emigration and immigration / Government policy; Europäische Union. Mitgliedsstaaten; European Union countries -- Emigration and immigration; European Union countries -- Emigration and immigration -- Government policy